AN EXPERIMENTAL STUDY OF B-, P- AND F-RICH SYNTHETIC GRANITE PEGMATITE AT 0.1 AND 0.2 GPA - Veksler I.V.; Thomas R. (My University, 2002)
Extreme enrichment in H2O, B, P and F is characteristic of many evolved granites and pegmatites. We report experimental phase relations of a synthetic peraluminous pegmatite spiked with P2O5, B2O3 and F (5 wt% of each), Rb2O, Cs2O (1 wt% of each) and Li2O (0.5 wt%). Experiments were carried out in H2O-saturated conditions in cold-seal rapid-quench pressure vessels at 0.1-0.2 GPa. Crystallisation starts at about 820 C with berlinite and topaz. Quartz appears at 700-750 C. Topaz is replaced by muscovite at about 600 C. At near-solidus temperatures (450-500 C) amblygonite, lacroixite and a Cs-bearing aluminosilicate crystallise. In all charges aluminosilicate melt coexists with low-density hydrous fluid and hydrosaline melt. The latter is strongly enriched in Na3AlF6 and H3BO3 components. Experimental evidence of the liquid immiscibility and mineral reactions documented in our study offers new explanations of many enigmatic features of natural pegmatites.